Assessing temporal and spatial variations in atmospheric dust over Saudi Arabia through satellite, radiometric, and station data. Issue 23 (11th December 2013) - Yu, Yan; Notaro, Michael; Liu, Zhengyu; Kalashnikova, Olga; Alkolibi, Fahad; Fadda, Eyad; Bakhrjy, Fawzieh
Abstract [1] Temporal and spatial variations in atmospheric dust over Saudi Arabia are studied for 2000–2010 using satellite and ground‐based aerosol optical depth (AOD) and station dust storm observations. These data sets show a consistent seasonal cycle in dust activity, which peaks in spring–summer in northern‐central Saudi Arabia and in early spring and summer across southern‐western Saudi Arabia, associated with strong winds and westerly transport, respectively. Over the desert regions, anomalies in dust activity from satellite and station observations are highly correlated on the monthly timescale and statistically consistent on the daily timescale. However, the coastal and mountainous regions exhibit limited consistency between these data sets, likely associated with the coarse spatial resolution and short sampling time in the satellite data, as well as non‐aeolian aerosol contamination. We conclude that satellite AOD is a reliable index for dust activity over desert regions but not over low dust, coastal, and topographically complex regions in Saudi Arabia.